Direct-Acting Oral Anticoagulants as Emerging Treatment Options for Heparin-Induced Thrombocytopenia. (June 2015) - Miyares, Marta A.; Davis, Kyle A.
Objective: To review the evidence for the use of the direct-acting oral anticoagulants (DOACs) in adult patients with heparin-induced thrombocytopenia (HIT).Data Source: A PubMed search (1950-February 2015) was collected using the terms heparin-induced thrombocytopenia, with dabigatran, rivaroxaban, or apixaban, or heparin-induced thrombocytopenia and target-specific anticoagulants, or heparin-induced thrombocytopenia and direct-acting oral anticoagulants, or heparin-induced thrombocytopenia and new oral anticoagulants .Study Selection and Data Extraction: All English-language articles were reviewed for inclusion. The references of included articles were reviewed for additional data.Data Synthesis: HIT is an immune-mediated, prothrombotic adverse reaction that requires not only discontinuation of heparin but also initiation of an alternative nonheparin anticoagulant to counter the effects of the autoimmune cascade. Pharmacotherapeutic management with argatroban is unpredictable and problematic. The DOACs display predictable pharmacokinetic and pharmacodynamic profiles and exhibit no interaction with platelet factor 4. Currently, the DOACs are approved by the Food and Drug Administration for venous thromboembolism, yet have limited evidence in both in vitro and clinical HIT studies.Conclusions: Though dabigatran, rivaroxaban, and apixaban have been used in case reports, currently data are not yet sufficient to recommend clinical use of these agents in the management of HIT. Future trial results may further substantiate management of HIT with use of the DOACs.